TOCILIZUMAB EFFICACY AND SAFETY IN PATIENTS WITH SEVERE SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS - E.I. Alexeeva; R.V. Denisova; S.I. Valieva; T.M. Bzarova; K.B. Isaeva; E.G. Chistyakova; T.V. Sleptsova; E.V. Mitenko (Вопросы современной педиатрии, 2011)
This article contains results of the research of tocilizumab treatment efficacy and safety in 39 patients with severe systemic juvenile idiopathic arthritis, resistant to standard immunosuppressive treatment. Tocilizumab efficacy analysis has shown 50% of patients with inactive disease after 6 months of treatment, and 57% of patients with inactive disease after 12 months. Among adverse events were mild and moderate infections and such laboratory abnormalities as low leukocyte and neutrophiles count.Key words: children, juvenile idiopathic arthritis, systemic arthritis, tocilizumab, treatment.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (3): 24–32)